Uso de biomarcadores en el diagnóstico y el tratamiento de la sepsis (2013)
ABSTRACT: Sepsis is a very complex clinical phenomenon in both its definition and pathophysiology. So far its diagnosis has been based only on clinical symptoms and signs together with the results of some laboratory tests. However, efforts are being done to find biomarkers that are able to identify sepsis or rule it out, and to serve as guide for treatment. Objective: This review describes the most thoroughly studied biomarkers of sepsis and their potential use, as well as the experience achieved in Medellín, Colombia, with research in this field. Methods: A search on this subject matter was carried out in PubMed, and a critical analysis was done of the most relevant papers found including those published in Colombia. Results and conclusions: More than 180 biomarkers have been studied, most of them for diagnostic and prognostic purposes. Unfortunately, none of them has exhibited the sensitivity and specificity required to be recommended for routine clinical practice. So far, procalcitonin has been the most promising biomarker. Doubtless, this line of research should be continued and reinforced.